Peningkatan Kinerja Sistem Keamanan Pada Proses pensinyalan Dalam Vertical Handover MIPv6 - Supriyanto Praptodiyono; Daniel Barita (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2020)
The development of mobile technology is increasing every year as well as users of mobile devices. Vertical Handover (VHO) is one of the technological developments that helps mobile users and communicate or share data easily with each other. VHO requires an IPv6 address on a mobile device called the mobile internet protocol (MIPv6). However, MIPv6 has a gap that makes it vulnerable to attack when carrying out a handover process, especially during the Binding Update process. One way to secure MIPv6 is to use the IPsec tunnel method with ESP header. The encryption that will be used in this study is 3DES and AES. Based on the research carried out AES encryption is superior to 3DES with throughoput values of 25.25 Mbit / s and 21,978 Mbit / s, respectively. With time generating 0.019 ms AES packet while 3DES requires 0.121 ms. Keywords: Vertical Handover, MIpv6, AES, 3DES.